Fiber-optic wireless sensor network using ultra-weak fiber Bragg gratings for vertical subsurface deformation monitoring - Liu, Su-Ping; Shi, Bin; Gu, Kai; Zhang, Cheng-Cheng; He, Jian-Hui; Wu, Jing-Hong; Wei, Guang-Qing (Natural hazards (Dordrecht), 2021)
The determination of subsurface deformation is critical to understanding the subsurface dynamic processes, but most of conventional monitoring methods still have challenges in remotely obtaining detailed data. Herein, a novel fiber-optic wireless sensor network using the ultra-weak fiber Bragg gratings technique was proposed. It allows real-time remote capture of subsurface deformation along the fiber-optic cables. Such a fiber-optic measurement system was employed in a borehole to a depth of 340 m in Cangzhou, China. Strain profiles were measured monthly with a spatial resolution of 5 m and strain resolution of 1 µε, and the development of all strata deformation in the aquifer systems was calculated from January 2019 to December 2019. It turns out that the subsidence rate in this area is approximate 9 mm/a, which agrees well with the result of extensometer measurements. The significant strata compaction in the second aquifer and the third aquitard rapidly increased from May 2019 to July 2019, which could be attributed to the decline in groundwater. It is concluded that the fiber-optic wireless sensor network accurately captures subsurface deformation development and helps to better elucidate the subsurface deformation mechanism and provide solutions for the prevention and mitigation.